The Impact Of Oyster Waste On The Social Environment Of The Community And Government Policies On Oyster Tree Control In Coppo Village, Barru District, Barru Regency - Pratiwi, Dian; Nurlia, Nurlia (SEAN Institute, 2024)
This study aims to find out the impact of oyster waste on the social environment of the community and to find out the policies of the village government on oyster waste. The method used is a qualitative research method, a source of data obtained by means of interviews, observations, and documentation. Data analysis uses data collection, data reduction, data preparation and conclusion extraction. The results of this study show that the negative impact of oyster waste in Deae on oyster sellers is the impact on the coral reef environment and the impact on humans such as being scratched by the skin of oyster shells if not wearing footwear, and the positive impact of oyster waste can be used as a landfill, cement mixture, and can be used as fertilizer. And the oyster waste control policy in Deae has not made specific rules for oyster waste control, and the results of this study show that this oyster waste can be used by remanaging it.